Altruistic Punishment in Elections - Jason A. Aimone; Luigi Butera; Thomas Stratmann (Center for Economic Studies and ifo Institute (CESifo), 2014)
Altruistic punishment is a fundamental driver for cooperation in human interactions. In this paper, we expand our understanding of this form of costly punishment to help explain a puzzle of voting behavior: why do people who are indifferent between two potential policy outcomes of an election participate in large-scale elections when voting is costly? Using a simple voting experiment, we show that many voters are willing to engage in voting as a form of punishment, even when voting is costly and the voter has no monetary stake in the election outcome. In our sample, we observe that at least fourteen percent of individuals are willing to incur a cost and vote against candidates who broke their electoral promises, even when they have no pecuniary interest in the election outcome.
Keywords: D73; D03; D63; 330; voting; elections; altruistic punishment